Factors associated with accidents and complications on third molar extraction: a literature review (Research, Society and Development, 2021)
Complications are what happen after the surgical procedure, while accidents are those that happen outside the planning in the transoperative period. The literature shows that, among the main accidents and complications during and after the third molar extraction procedure, there are fractures of dental element(s), inferior alveolar nerve paresthesia, oral-sinusal communication, hemorrhage, hematoma, alveolitis, pain, edema, trismus, joint dislocation and mandible fracture. For this reason, it is essential that the dental surgeon seeks prior theoretical and practical knowledge of the dental procedures to be performed, as well as means of conduct and care in cases of complications. This paper reports a narrative literature review on complications and surgical accidents of third molars, aiming to discuss the factors that lead to their emergence. The databases selected for the study were Academic Google and Pubmed, being selected according to established inclusion and exclusion criteria.